Terapia Respiratoria y su incidencia en el manejo del síndrome de obstrucción nasal del lactante comunidad las Malvinas cantón ventanas provincia Los Rios primer semestre 2015 - Lema Sánchez, Tatiana Filadelfia (2015)
Nasal obstruction syndrome is a condition in which not enough air reaches the lungs in an individual at rest breathing only through your nose. Title: "Management of respiratory therapy and its effect on nasal obstruction syndrome in infants". An explanatory descriptive study was conducted to establish the incidence of respiratory therapy in the management of nasal obstruction in infants community Las Malvinas, Canton Ventanas, Los Rios province, first half 2015